2012
DOI: 10.1016/j.molcel.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

LC3C, Bound Selectively by a Noncanonical LIR Motif in NDP52, Is Required for Antibacterial Autophagy

Abstract: SummaryAutophagy protects cellular homeostasis by capturing cytosolic components and invading pathogens for lysosomal degradation. Autophagy receptors target cargo to autophagy by binding ATG8 on autophagosomal membranes. The expansion of the ATG8 family in higher eukaryotes suggests that specific interactions with autophagy receptors facilitate differential cargo handling. However, selective interactors of ATG8 orthologs are unknown. Here we show that the selectivity of the autophagy receptor NDP52 for LC3C i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
296
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(309 citation statements)
references
References 58 publications
11
296
1
1
Order By: Relevance
“…Binding of ALFY to GABARAP facilitates the recruitment of LC3B to ALFY and p62-positive structures, further indicating that a high-affinity LIR-Atg8 protein interaction is required for exclusive autophagy. In line with this, interaction of the ubiquitin-binding autophagy receptor NDP52 (also known as CALCOCO2) with LC3C was found to be required for the recruitment of other Atg8 family members to cytosolic Salmonella Typhimurium (von Muhlinen et al, 2012). Taken together, these studies suggest that an initial interaction between an Atg8 protein and a LIR-containing receptor forms a platform for further phagophore expansion and cargo sequestration.…”
Section: Membrane Modeling In Selective Autophagymentioning
confidence: 58%
“…Binding of ALFY to GABARAP facilitates the recruitment of LC3B to ALFY and p62-positive structures, further indicating that a high-affinity LIR-Atg8 protein interaction is required for exclusive autophagy. In line with this, interaction of the ubiquitin-binding autophagy receptor NDP52 (also known as CALCOCO2) with LC3C was found to be required for the recruitment of other Atg8 family members to cytosolic Salmonella Typhimurium (von Muhlinen et al, 2012). Taken together, these studies suggest that an initial interaction between an Atg8 protein and a LIR-containing receptor forms a platform for further phagophore expansion and cargo sequestration.…”
Section: Membrane Modeling In Selective Autophagymentioning
confidence: 58%
“…The amount of LC3-II becomes a marker for the formation of autophagosomes. The recent study performed on human cells infected with S. Typhimurium, showed that LC3C was required for antibacterial autophagy because in its absence the remaining ATG8 orthologs did not support efficient autophagy of intracellular bacteria [61]. The subsequent reports indicated that differential involvement of LC3 paralogs, LC3-II and LC3C, can classify autophagy in two separate programs that execute either pro-or anti-tumorigenic activities in renal cell carcinoma cells [62,63].…”
Section: Autophagy Signal Transduction and Corresponding Morphologicamentioning
confidence: 99%
“…20,[30][31][32] Recently, a noncanonical LIR motif, which solely comprises 3 consecutive hydrophobic residues (LVV), has been found in the autophagy receptor CALCOCO2/NDP52. 33 This atypical LIR motif (termed as CLIR) exclusively interacts with the Atg8-family member, LC3C, and endows CALCOCO2 with a unique function in xenophagy. 33 Although the LIR-mediated interactions of Atg8-family proteins with LIR-containing proteins involved in autophagosome biogenesis and autophagic cargoes recruitment are well characterized, no relevant detailed information related to autophagic vesicle trafficking has been available yet.…”
Section: Introductionmentioning
confidence: 99%